A Comparative Analysis of Legal Products on the Development of Productive Waqf in Indonesia and Malaysia - M. Roem Syibly; Cahya Wulan Ndini; Nurul Hidayawatie Mustaffa; Muhammad Rabbani Bin Zulkifle (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2022)
Indonesia and Malaysia generally have the same Islamic character and history, so the development of Islamic law also has the same roots. Then there were differences in the development of Islamic law, including the law on waqf, which was caused by differences in colonial history. The Dutch colonized Indonesia, and Malaysia was colonized by the British. Therefore, they have different systems and state administrations. This study aims to explain how much support for positive legal products that regulate waqf impacts the development of productive waqf instruments in Indonesia and Malaysia, although with different legal systems. This research is literature research with a juridical-normative approach with a qualitative model. Analysis of the data used is the interactive analysis model of Miles and Huberman. The study results in show that in Indonesia and Malaysia, waqf legal products have existed since the sultanate era, colonial era, and independence era. Waqf legal products in Indonesia regulate more about waqf of immovable objects, which are regulated in different legal products. However, since the birth of the Waqf Law in 2004, waqf has not only focused on immovable objects but also movable and productive objects following the development of the financial world. And business. Likewise, in Malaysia, the legal product of waqf is included in family law which is regulated in the law in each different country, including the territory of the alliance. Productive waqf has also penetrated productive economic efforts by the purpose of waqf.